(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The article discusses the changes that occur in the cardiovascular system during pregnancy, as well as physical exercises that are prescribed during pregnancy to prepare the cardiovascular system for childbirth.